Microbiological quality assessment of locally vended and commercially packed fruit juices in Chittagong city of Bangladesh - Sultana, F; Marzan, LW; Mina, SA (Journal of Bio-Science, 2019)
Microbiological investigation has been undertaken for freshly prepared and commercially packed fruit juices of Chittagong city, Bangladesh. Physicochemical analysis as pH, sugar content, total soluble solid (TSS), total dissolved solid (TDS), acidity, moisture content and microbiological parameters i.e. total viable count (TVC), total coliform count (TCC), fecal coliform count (FCC), total staphylococcal count (TSC), Vibrio spp., Salmonella spp., Shigella spp. were examined for all samples. No microorganisms were found positive in packed fruit juice samples, whereas the range of TVC, TCC, and TSC were found to be 2.0 × 103 - 1.0 × 105, 0.15 × 102 - 11 × 102 and 1.0 × 102 - 2.0 × 104 cfu/ml respectively, though there was no detectable FCC and Salmonella, Shigella for vended samples. Human pathogenic Vibrio cholerae, Klebsiella pneumoniae and Staphylococcus aureus were identified by biochemical tests and further confirmed by 16S rDNA sequence analysis. Antibiotic sensitivity of Klebsiella pneumoniae and Staphylococcus aureus were found against ciprofloxacin, imipenem, gentamicin, levofloxacin except amoxicillin; whereas Vibrio cholerae showed resistant to all above antibiotics. Hence, proper awareness and regular monitoring are required during vended fruit juice handling as antibiotic resistant pathogenic bacteria can easily spread through the contaminated fruit juices to the consumers. J. bio-sci. 27: 43-58, 2019